Regio‐ and Stereospecific Prenylation of Flavonoids by Sophora flavescens Prenyltransferase. Issue 9 (4th June 2013) - Chen, Ridao; Liu, Xiao; Zou, Jianhua; Yin, Yunze; Ou, Bin; Li, Jianhua; Wang, Ruishan; Xie, Dan; Zhang, Peicheng; Dai, Jungui
Abstract Prenylflavonoids are valuable natural products that are widely distributed in plants. They often possess divergent biological properties, including phytoestrogenic, anti‐bacterial, anti‐tumor, and anti‐diabetic activities. The reaction catalyzed by prenyltransferases represents a Friedel–Crafts alkylation of the flavonoid skeleton in the biosynthesis of natural prenylflavonoids and often contributes to the structural diversity and biological activity of these compounds. However, only a few plant flavonoid prenyltransferases have been identified thus far, and these prenyltransferases exhibit strict substrate specificity and low catalytic efficiency. In this article, a flavonoid prenyltransferase from Sophora flavescens, SfFPT, has been identified that displays high catalytic efficiency with high regiospecificity acting on C‐8 of structurally different types of flavonoid (i.e., flavanone, flavone, flavanonol, and dihydrochalcone, etc.). Furthermore, SfPFT exhibits strict stereospecificity for levorotatory flavanones to produce (2S)‐prenylflavanones. This study is the first to demonstrate the substrate promiscuity and stereospecificity of a plant flavonoid prenyltransferase in vitro. Given its substrate promiscuity and high catalytic efficiency, SfFPT can be used as an environmentally friendly and efficient biological catalyst for the regio‐ and stereospecific prenylation of flavonoids to produce bioactive compounds for potential therapeutic applications.